2019
DOI: 10.3390/nu11050966
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Omega-3 and Omega-6 Polyunsaturated Fatty Acids on the Production of Cyclooxygenase and Lipoxygenase Metabolites by Human Umbilical Vein Endothelial Cells

Abstract: Although the correlation between polyunsaturated fatty acids (PUFA) and the production of pro- and anti-inflammatory metabolites is well documented, little is known about the simultaneous effect of different PUFA on the production of cyclooxygenase and lipoxygenase metabolites. The present research examines the association between different omega-3 (ω-3) and omega-6 (ω-6) PUFA and the release of four cyclooxygenase and six lipoxygenase metabolites in cell medium by human umbilical vein endothelial cells (HUVEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 49 publications
2
25
0
1
Order By: Relevance
“…Studies carried out worldwide suggest that the use of ω‐3, mainly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have anti‐inflammatory properties [23], inhibit platelet aggregation, improve endothelial injury and stabilize atherosclerotic plaques in the stroke [24, 25]. In addition, some studies indicate that food supplementation with ω‐3 has a modulating effect, since in addition to the anti‐inflammatory effects, this fatty acid induces the synthesis of anti‐inflammatory mediators such as resolvins, protectins and maresines and reduces the activation of microglia and NF‐κB [14, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out worldwide suggest that the use of ω‐3, mainly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have anti‐inflammatory properties [23], inhibit platelet aggregation, improve endothelial injury and stabilize atherosclerotic plaques in the stroke [24, 25]. In addition, some studies indicate that food supplementation with ω‐3 has a modulating effect, since in addition to the anti‐inflammatory effects, this fatty acid induces the synthesis of anti‐inflammatory mediators such as resolvins, protectins and maresines and reduces the activation of microglia and NF‐κB [14, 26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that high levels of PUFAs and a high ω‐6/ω‐3 ratio in PN may contribute to increased incidence of cholestasis, steatosis, sepsis, changes in neutrophil function, and upregulation of matrix metalloproteinases (MMPs) . The ω‐6 PUFA arachidonic acid (AA) produces prostaglandins (PGs), thromboxanes (TXs), 5‐hydroxy‐eicosatetraenoic acid, and other 4‐series leukotrienes (LTs) that are proinflammatory . The ω‐3 fatty acid eicosapentaenoic acid (EPA) produces 3‐series PGs, TXs, and 5‐series LTs, which have less detrimental effect than AA‐derived mediators have …”
Section: The Role Of Lipidsmentioning
confidence: 99%
“…EPA competitively inhibits prostaglandin E2 formation by cyclooxygenase (COX) 1/2 from AA, and it produces less-inflammatory prostaglandin E3, thereby showing an anti-inflammatory effect, inhibition of monocyte adhesion and platelet aggregation, and improvement of endothelial injury [67,68]. EPA also decreases the production of mediators and enzymes from inflammatory cells such as macrophages and stabilizes atherosclerotic plaques [22,23,24].…”
Section: Biological Effects Of Omega-3 Pufas For Strokementioning
confidence: 99%
“…There is evidence that DHA suppresses inflammation more potently than EPA [69,70]. Importantly, EPA and DHA are metabolized via the COX and lipoxygenase pathways into a new class of lipid mediators [67,68]. Specialized pro-resolving lipid mediators, including resolvins, maresins, and protectins, are synthesized from n-3 PUFAs.…”
Section: Biological Effects Of Omega-3 Pufas For Strokementioning
confidence: 99%